AKIBAT HUKUM NOMINEE AGREEMENT TERHADAP JUAL BELI TANAH OLEH WARGA NEGARA ASING DENGAN PINJAM NAMA - Cahaya Dewi Savitri, A A Sagung; Putri M.E Purwani, Sagung (Kertha Semaya : Journal Ilmu Hukum, 2013)
Legal consequences nominee agreement to purchase land by foreign nationals with borrowed names, written with the aim to determine the legal affect of a nominee agreement on the sale and purchase of land by foreigners to borrow the name. in this study using normative research, which is where the writing refers to the apporoach to the normative aspects of the legislation and the book / material law. Conclusion of this paper is flawed agreement is considered as null and void acts.
Keywords: Nominee Agreement, legal consequences, null and void